Pengaruh Persepsi Konsumen dan Promosi terhadap Keputusan Pembelian Studi Empiris pada Pengguna Shopee - Firas, Rakka; Rahmadani, Novitri; Marsya, Ayundia Putri; Ulinnuha, Rismathul; Yulianto, Yulianto (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The goal of this research is to test and demonstrate how consumer perceptions and promotions affect Shopee buying decisions. Students enrolled in the Management Study Program at Universitas Pamulang's Faculty of Economic and Business make up the study's population. A sample of 74 respondents was employed in this investigation. Purposive sampling combined with nonprobability sampling is the research methodology employed. The study's findings demonstrated the connection between the dependent variable, purchase decision and the independent variable, consumer perception and promotion. The T test, based on partial testing, demonstrates that consumer perception significantly and favourably influences purchasing decisions. Additionally, the promotion variable is acquired by demonstrating that the promotion significantly and favourably influences consumers' decisions to buy. It is possible to draw the conclusion that factors related to customer perception and promotions significantly and favourably influence purchasing decisions. Customer perception and promotion account for 57.2% of the Coefficient of Determination (R Square) of 0.572, which explains the purchase decision, other factors not included in this study account for the remaining 42.8%.